Fracture Resistance of Residually-Stressed Ceramic Laminated Structures - Gogotsi, G.A.; Lugovoi, N.I.; Slyunyaev, V.N. (Проблемы прочности, 2004)
We have studied the effect of residual stresses on
fracture resistance and crack arrest behavior of
asymmetric ceramic laminated Si3N4 /Si3N4 -TiN
structures. Using a compliance method, we assessed
is the technique of R-curve construction for
laminar composites. For laminar structures with
layers varying by their elastic characteristics we
developed an analytical method for calculation of
“fracture resistance - crack length” dependence.
The method applicability is verified by calculation
of stress intensity factors for laminar specimens
with edge crack. The calculated results are compared
to the experimental data. Изучено влияние остаточных напряжений на сопротивление разрушению и остановку трещины
в несимметричных слоистых структурах Si3N4 /Si3N4 -TiN. Оценена методика определения
R-кривых слоистых композитов с использованием метода податливости. Разработан
аналитический метод расчета зависимости сопротивления разрушению от длины
трещины в слоистых структурах со слоями, имеющими различные упругие характеристики.
Применимость метода проверена путем расчета коэффициентов интенсивности напряжений
для слоистых образцов с краевой трещиной. Полученные результаты сопоставлялись
с данными механических испытаний. Розглядається вплив залишкових напружень на опір руйнуванню і зупинку
тріщини в несиметричних шаруватих структурах Si3N4 /Si3N4 -TiN. Проаналізовано
методику визначення ^-кривих шаруватих композитів із використанням
методу піддатливості. Розроблено аналітичний метод розрахунку
залежності опору руйнуванню від довжини тріщини в шаруватих структурах,
що мають шари з різними пружними характеристиками. Застосовність
методу перевірено шляхом розрахунку коефіцієнтів інтенсивності
напружень для шаруватих зразків із крайовою тріщиною. Отримані результати
зіставляються з даними механічних випробувань.